Geosciences in Academic Publications - Radchenko, A.I.; Didenko, Yu.V. (Science and Innovation, 2024)
Using materials of annual reports made by R&D institutions of the NAS of Ukraine, annual annotated book catalogues and catalogues of periodicals of the NAS of Ukraine scientific geological publications issued in 2005—2015 have been analyzed. The contribution of publishing products issued by geology-oriented institutions to the general totality of the Academy’s publications has been discussed. The distribution of publishing products of geology-oriented institutions within the criteria of publication type and separately foreign publications has been considered. The participation of geology-oriented institutions of the NAS of Ukraine in all-academic publishing projects within the framework of the state order of the NAS of Ukraine has been presented. The results of collaboration between Akademperiodyka Publishing House of the NAS of Ukraine and non-NAS geology-oriented institutions have been described. The current situation related to the academic geology-oriented periodicals has been analyzed with attention focused on the journals of the Geosciences Department of the NAS of Ukraine.